The World of African Storytelling - Isidore Okpewho (University of Edinburgh, 2009)
My favorite introduction to a discussion of African storytelling is to recall a setting that Oyekan Owomoyela sketched out many years ago from his experience in the Yoruba city of Ibadan in western Nigeria. It is of a traditional family relaxing in their premises at the end of a hardworking day. After the evening meal, the members of the family gather on a porch and if there is moonlight, the younger members gather in the courtyard to play games like hide and seek. On the porch, the entertainment begins with riddles. What dines with an oba (paramount chief of a community) and leaves him to clear the dishes? A fly. What passes befor the oba’s palace without making obeisance? Rain flood. On its way to Oyo its face is towards Oyo, on its way from Oyo its face is still towards Oyo. What is it? A double-faced drum. After a few riddles, the tales begin (Owomoyela 264-265).